Measuring Educator Satisfaction of Learning Analytics for Online Learning Systems in Malaysia - Shahril Khuzairi N.M.; Cob Z.C.; Hilaluddin T. (Springer Science and Business Media Deutschland GmbH, 2024)
The use of online learning systems has proliferated, which has caused an explosion of generated data. The use of learning analytics to sort through this data for valuable performance-enhancing insights is fast becoming the norm. Although many research works are published on learning analytics, there is still a lack of research that identifies learning analytics features as a significant influencing factor in improving educator satisfaction. The purpose of this paper is to examine the influence of learning analytics features that leads to a successful implementation of learning analytics for online learning systems. A survey involving 134 educators from 17 public and private higher education institutions in Malaysia was conducted. Data were analyzed using the structural equation modeling method, and the results showed a significant influence of learning analytics on educator satisfaction. This empirical evidence gives insight into the development of successful learning analytics for online learning systems. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.